Afro-descendant social organizations in the municipality of Florencia (Colombia): Achievements, difficulties and challenges - Sánchez Castillo, Verenice; Gómez Cano, Carlos Alberto; Moreno González, Yady Melissa (Cooperativismo & Desarrollo, 2017)
Introduction: Afro-descendant organization in the municipality of Florencia, Caquetá (Colombia), evidences the need to unify in order to achieve recognition and overcome the struggle for their rights. Although the interviewed subjects declare that there is little racial discrimination in the department, the necessity to attain visibility and recognition has lead to the formation of three Afro-descendant organizations, as well as to their continued consolidation over time. The interest of this manuscript is precisely to systematize these three organizational experiences based on their history, achievements, difficulties and the main challenges they face as a group. Methodology: The work is eminently qualitative. Data were obtained using instruments such as interviews and documentary review. Results: Within the main findings, it is evident that the existing organizations result from internal fragmentation of the organization that appeared fist. Nevertheless, all of them have similar objectives. The biggest difficulties they face relate to the scarce income available for their sustenance and for offering more supporting to their partners. Conclusions: The Afro-descendant organizations’ achievements include having been recognized by the Ministry of Internal Affairs, positioning themselves in the Caquetá society and having been taken in account for regional decision making. The difficulties faced continue to be related to the limited economic resources available and tough access to rural and urban socio-economic inclusion projects. The lack of internal articulation must also be mentioned, since the interviewed subjects believe particular interests in some occasions prevail over group objectives and benefits. The three organizations under study agreed in these points.